2009
DOI: 10.1172/jci33338
|View full text |Cite
|
Sign up to set email alerts
|

Persistent eNOS activation secondary to caveolin-1 deficiency induces pulmonary hypertension in mice and humans through PKG nitration

Abstract: Pulmonary hypertension (PH) is an unremitting disease defined by a progressive increase in pulmonary vascular resistance leading to right-sided heart failure. Using mice with genetic deletions of caveolin 1 (Cav1) and eNOS (Nos3), we demonstrate here that chronic eNOS activation secondary to loss of caveolin-1 can lead to PH. Consistent with a role for eNOS in the pathogenesis of PH, the pulmonary vascular remodeling and PH phenotype of Cav1 -/-mice were absent in Cav1 -/-Nos3 -/-mice. Further, treatment of Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
305
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(324 citation statements)
references
References 61 publications
18
305
1
Order By: Relevance
“…Interestingly, double knockout mice (caveolin-1 and eNOS) do not develop PH. The eNOS transgenic mice with increased endothelial eNOS expression, however, do not develop PH and are protected from hypoxia-induced PH (96,132,137). These studies indicate that caveolin-1 is essential not only for inhibiting proliferative pathways but also for maintaining physiological function of eNOS.…”
Section: Disruption Of Ec Membranementioning
confidence: 84%
See 2 more Smart Citations
“…Interestingly, double knockout mice (caveolin-1 and eNOS) do not develop PH. The eNOS transgenic mice with increased endothelial eNOS expression, however, do not develop PH and are protected from hypoxia-induced PH (96,132,137). These studies indicate that caveolin-1 is essential not only for inhibiting proliferative pathways but also for maintaining physiological function of eNOS.…”
Section: Disruption Of Ec Membranementioning
confidence: 84%
“…Reexpression of endothelial caveolin-1 restores vascular and cardiac pathology and dysfunction. Interestingly, increased caveolin-1 has been shown to prevent eNOS-derived ROS by forming a complex with free eNOS (62,90,137). Furthermore, inhibition of eNOS by N G -nitro-L-arginine methyl ester prevents vascular remodeling and PH in caveolin-1 Ϫ/Ϫ mice.…”
Section: Disruption Of Ec Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Functional connections between caveolin (cav) and oxidative stress have emerged in several recent studies. The loss of caveolin-1 (cav-1) increases NO and/or reactive oxygen species (ROS) production [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that Cav1 -/-mice develop PH (greater than 80% increase of pulmonary arterial pressure) [22]. These mice exhibit right ventricle hypertrophy associated with marked increase of right ventricular contractility and diastolic function [22] and increased pulmonary vascular resistance as well as pulmonary vascular remodeling evident by increased medial thickness and muscularization of distal pulmonary vessels [23]. Studies have also shown decreased pulmonary artery density and defective pulmonary artery filling [24].…”
Section: Genetic Deletion Of Cav1 Induces Ph In Micementioning
confidence: 99%